Net carbon ecosystem exchange during 24 years in the Sorø Beech Forest – relations to phenology and climate. Issue 1 (1st January 2020) - Pilegaard, Kim; Ibrom, Andreas
Abstract: The carbon sequestration of plants through photosynthesis is responsible for removal of a substantial amount of the man-made CO2 emissions to the atmosphere. In recent years this so-called land-sink has removed about 30% of the man-made emissions to the atmosphere, with forests being the most important sinks. The land-sink is, however, vulnerable to changes in the environment, such as the atmospheric composition, climate change, and extreme events like storms and droughts. It is therefore important to study the effects of such change on terrestrial ecosystems to provide the basis for predicting the future of the sink. We here report the results of continuous CO2 flux measurements over a Danish beech forest during the years 1996–2019. Over the years the forest acted as a sink of CO2 with a net carbon sequestration ranging from about zero to 400 g C m –2 yr −1. We found significant trends in net ecosystem exchange (NEE) (increasing in absolute terms with 15 g C m –2 yr 2 ), gross ecosystem exchange (GEE) (increasing with 25 g C m –2 yr –2 ), and ecosystem respiration (RE) (increasing with 10 g C m –2 yr –2 ). A prolonged growing season explained 73% of the increase in NEE. The increasing CO2 concentration in the atmosphere and a subsequent increase in photosynthetic capacity together with warming are the most likely main causes of the increased carbon uptake. The severe drought in the summer of 2018 resulted in a reduction of the annual NEE of 25%.